MgO Nanomaterials Improve Fibroblast Adhesion and Proliferation. Issue 1722 (11th May 2015) - Hickey, Daniel J.; Webster, Thomas J.
ABSTRACT: Magnesium (Mg) plays an important role in the body mediating cell-extracellular matrix (ECM) interactions, bone apatite structure and density, and nucleic acid chemistries. While Mg has been investigated as a biomaterial for bone applications, it has not been studied for applications within soft tissues. This study investigated, for the first time, the response of fibroblasts to magnesium oxide (MgO) nanoparticles for soft tissue engineering applications. Primary human dermal fibroblasts were cultured both on tissue culture polystyrene in media supplemented with MgO nanoparticles as well as on poly-L-lactic acid (PLLA)-MgO nanoparticle composites. As this study was conducted concurrently with a study aimed at bone tissue engineering, hydroxyapatite (HA) nanomaterials were used for comparison. Results showed for the first time that fibroblasts adhered onto MgO-containing composites roughly three times better than HA-PLLA samples and roughly 4.5 times better than plain PLLA samples. Fibroblasts also proliferated to statistically higher densities when cultured in medium supplemented with MgO nanoparticles compared to un-supplemented medium and medium supplemented with HA nanoparticles. These preliminary results together suggest that MgO nanoparticles should be further investigated as materials to improve the regeneration of soft tissues as well as bone.